Tinder Tales: An Exploratory Study of Online Dating Users and Their Most Interesting Stories. Issue 9 (2nd September 2021) - Fansher, Ashley K.; Eckinger, Sara
ABSTRACT: The present study examines the differences between users and non-users of mobile-based dating applications, along with individual user experiences. To better understand the typical online dating application consumer, this research utilized quantitative analyses to compare traditional college-age users versus non-users on behavioral and attitudinal measures. Qualitative coding took place to analyze open-ended survey responses from participants regarding personal experiences. Those who use mobile-based dating applications were significantly different from non-users on all variables examined, including rates of negative drinking behaviors, drug use, sexual compulsivity, sexual deception, and negative sexual behaviors. The review of qualitative responses revealed users experiencing a wide range of negative behaviors including stalking, consensual and non-consensual explicit photo sharing, consensual and non-consensual message sharing, and deception. This article provides a framework for the identification of potential risks of using online dating applications and highlights prevention programming that will enhance the awareness of problematic online dating behaviors.